The Writing Process: A Means to Improving the Writing Skills of the Student-Athlete - Funk, Gary D.; Haseltine, Becky (My University, 1987)
The authors recommend using workshops, study hall, and tutoring programs to lead athletes through a four-stage writing process.
Keywords: skills; academic support